THE PEDAGOGICAL SKILLS OF THE HIGH SCHOOL TEACHER: THE THEORETICAL JUSTIFICATION OF THE MODERN REQUIREMENTS - Oksana Vladimirovna Sitnikova (Вестник Северо-Кавказского федерального университета, 2022)
The author reveals the specifics of professional high school teacher in accordance with the modern requirements, which becomes a multi-vector activity by its definition. It is focusing the attention on the personality of the teacher and on the phenomenon of pedagogical skills, making pedagogical work as the arts.